100 cases in clinical pharmacology, therapeutics and prescribing - Layne, Kerry; Ferro, Albert (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2020)
100 Cases in Clinical Pharmacology, Therapeutics and Prescribing explores scenarios commonly seen by medical students and junior doctors in the ward, emergency department, outpatient clinic or in general practice in which an understanding of pharmacology and sound prescribing practice is central to successful clinical management and safe patient care. A succinct summary of the patient's history, examination and any initial investigations is followed by questions on the diagnosis and management of the case. The answer includes a detailed discussion on each topic, providing practical advice on how to deal with the challenges that occur when prescribing, including planning, drug calculations, prescription review and adverse drug reactions. The book will be invaluable during clinical placements and is an ideal companion during preparation for the Prescribing Safety Assessmentexamination.Making speedy and appropriate clinical decisions, and choosing the best course of action to take as a result, is one of the most important and challenging parts of training to become a doctor. These true-to-life cases will teach students and junior doctors to prescribe appropriately, and to hone their diagnostic and management skills.
Includes index.
OCLC-licensed vendor bibliographic record.
Keywords: Clinical pharmacology; Clinical pharmacology -- Case studies; MEDICAL / Clinical Medicine; MEDICAL / Pharmacology; MEDICAL / Toxicology